‘Si RT’ application to simplify communication and transparency of information in the pandemic era - Selvia Ferdiana Kusuma; Agustono Heriadi; Benni Agung Nugroho; Ellya Nurfarida; Ratna Widyastuti (Community Empowerment, 2022)
Rukun Tetangga (RT) is the forefront of government services to the citizens as the RT's position is in the midst of society. Communication and information transparency are the main assets for the implementation of good governance. The covid-19 pandemic has changed a lot in human behavior. There are many restrictions to break the chain of Covid-19, for example, there are no crowds, maintain the distance, and other restrictions. Of course, this will complicate the RT's role in communicating and delivering information to residents. In addition, restrictions on social activities also force citizens not to be able to socialize freely with each other. The solution offered to solve this problem is the creation of an RT information system website which aims to facilitate communication and information transparency in the pandemic era. In addition, there is also assistance in the use of information systems to ensure that all citizens can use the information system. Based on the evaluation, the solutions offered are proven to facilitate communication and information transparency between citizens and between heads of RT and citizens in the pandemic era.